Customer's satisfaction towards services offered by Bintulu Port / Mohamad Azahan Mohammad Othman - Mohammad Othman, Mohamad Azahan (2015)
The purpose of this study is to identify customer's satisfaction towards service offered by Bintulu Port. The significance of this research is to give an opportunity to outpatient's customers to express their satisfaction towards the services that they received from Bintulu Port. The factors has been set as the independent variables, while customer's satisfaction is dependent variables. The objective of this research is to identify the relationship between reliability and customer's satisfaction, to identify the relationship between tangibility and customer's satisfaction and to identify the relationship between responsiveness and customer's satisfaction. The survey involves 100 respondents which are the customers pf Bintulu port. Data were obtained using primary and secondary data. The data was analyzed using SPSS software to obtain Frequencies, Reliability and Correlation analysis. The result are all independent variables have a significance relationship with customer's satisfaction. Based on study, responsiveness has been proven as the most important decision in customer's satisfaction.